2022
DOI: 10.1039/d1ew00957e
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of microbial native consortia efficient for textile wastewater degradation

Abstract: A comprehensive study on the degradation of pure textile effluent by two native bacterial consortia was conducted. Consortia composition, structure and dynamics towards effluent biodegradation and toxicity analyses were conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…These results are consistent with the finding of Wang et al [10], who reported that Kosakonia cowanii was inoculated into food wastewater to prepare a phosphate-solubilizing bacteria (PSB) liquid fertilizer. Single and mixed bacteria were conducive to degrading the organic matter in BBPW without additional nutrient sources; thus, it is convenient for microbial utilization [33].…”
Section: Biological Treatment Of the Bamboo Shoot Wastewatermentioning
confidence: 99%
“…These results are consistent with the finding of Wang et al [10], who reported that Kosakonia cowanii was inoculated into food wastewater to prepare a phosphate-solubilizing bacteria (PSB) liquid fertilizer. Single and mixed bacteria were conducive to degrading the organic matter in BBPW without additional nutrient sources; thus, it is convenient for microbial utilization [33].…”
Section: Biological Treatment Of the Bamboo Shoot Wastewatermentioning
confidence: 99%